Infância, aprendizagem e cultura: as crianças pataxó e as práticas sociais do Guarani - Luciano Silveira Coelho (2011)
This research was conducted in Guarani, one of the pataxó villages located in the Indigenous Land Fazenda Guarani, nearby Carmésia. The aim of this study was to highlight some fundamental aspects of learning of the pataxó children in their daily practices. To do so, it was necessary to approach the contemporary ethnological productions that have researched indigenous childhood under an analytical perspective and that see children as social and autonomous subjects. The theoretical grounds for such analysis were based on the anthropological productions about human learning, and more emphatically on the theories of Jean Laves Situated Learning and on Tim Ingolds ecological approach . The convergence of such references offers a theoretical framework that points to paths to understand learning as an essentially social process and knowledge as something that establishes and constitutes itself in the practice of everyday life. This theoretical contribuition has stressed fundamental aspects regarding the engagement of the pataxó children in six practices present in this village: hunting, farm work, the production and sales of handicrafts, household chores, soccer and play. It was observed that the involvement of the pataxó children in their daily lives is facilitated by their proximity to the adults and by their access to different areas in the village. We can conclude that the pataxó children are constantly involved in an interesting and complex environment that provides them with innumerable ways of learning that do not need a deliberate teaching to happen.